2021
DOI: 10.5312/wjo.v12.i6.412
|View full text |Cite
|
Sign up to set email alerts
|

Trends in leadership at orthopaedic surgery sports medicine fellowships

Abstract: BACKGROUND Fellowship directors (FDs) in sports medicine influence the future of trainees in the field of orthopaedics. Understanding the characteristics these leaders share must be brought into focus. For all current sports medicine FDs, our group analyzed their demographic background, institutional training, and academic experience. AIM To serve as a framework for those aspiring to achieve this position in orthopaedics and also identify opportunities to improve the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…This could be due to personal connections, prior training, or research relationships created before achieving the leadership role. Similarly, in orthopedic sports medicine, 22% of FDs worked at the same institution they completed fellowship at [ 4 ]. This observation is even more striking in the surgical sub-specialty of cardiothoracic surgery, where 60% of FDs stay in the same region, and 30% had institutional exposure to their program via medical school or training [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to personal connections, prior training, or research relationships created before achieving the leadership role. Similarly, in orthopedic sports medicine, 22% of FDs worked at the same institution they completed fellowship at [ 4 ]. This observation is even more striking in the surgical sub-specialty of cardiothoracic surgery, where 60% of FDs stay in the same region, and 30% had institutional exposure to their program via medical school or training [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the characteristics and attributes that breast surgical oncology FDs share may allow trainees, as well as burgeoning leaders, to better understand how these programs have been able to develop excellent breast surgeons. There have been a number of similar leadership papers published in accredited specialties that may now further serve as a roadmap for future leaders [ 4 9 ]. No previous study has analyzed demographics and prior training of FDs in the field of breast surgical oncology.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29] Bastian et al 29 analyzed 2,061 faculty members from 120 orthopaedic surgery residency programs and reported that academic ranks increased as research productivity increased for assistant professors, associate professors, professors, and chairs. Ence et al 30 analyzed 4,663 orthopaedic surgeons across 142 academic institutions and reported that research productivity and longer career duration correlated independently with higher academic rank for orthopaedic surgeons.Various orthopaedic academic leadership studies have described the high research productivity of current fellowship directors for subspecialties such as spine, 31 sports medicine, 32 arthroplasty, 33 and pediatrics 34 as a common characteristic.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Only three recent studies have examined the demographic trends among radiology director positions [3][4][5]. Moreover, other studies examining FDs in different subspecialties such as orthopedic surgery, ophthalmology, and cardiothoracic surgery were published recently [6][7][8][9][10]. In all of these surgical subspecialties, there were a larger number of male directors compared to females.…”
Section: Introductionmentioning
confidence: 99%
“…In all of these surgical subspecialties, there were a larger number of male directors compared to females. A study of sports medicine orthopedic surgeons observed a disproportionate proportion of male FDs (97.5%) with an average age of 56 years [ 9 ]. Ophthalmology showed a similar distribution with the majority being males (72%) with an average age of 50 years [ 7 ].…”
Section: Introductionmentioning
confidence: 99%